An Uncommon Presentation of Neuro-Behçet Syndrome Mistaken for West Nile Encephalitis - Megan Dell; Natalie Reed; Anika Noorali; Andrew Perry; Banks Kooken (Annals of Internal Medicine: Clinical Cases)
Behçet disease is relapsing and remitting systemic vasculitis that can affect any blood vessel. It is known to produce recurrent oral and genital aphthous ulcers; however, it can affect any organ system. This is a case of a 36-year-old man who was readmitted from an acute rehabilitation facility with worsening encephalopathy and odynophagia. Magnetic resonance imaging scan of the brain found hyperintensities in the thalami, midbrain, and pons. Findings of a lumbar puncture demonstrated a mixed inflammatory process. His symptoms were not responsive to any antimicrobial agents. Given the development of genital and oral lesions, characteristic neuroimaging changes, and profound response to steroids, neuro-Behçet was confirmed.